2020
DOI: 10.1002/ange.202008604
|View full text |Cite
|
Sign up to set email alerts
|

PlatinER: A Highly Potent Anticancer Platinum(II) Complex that Induces Endoplasmic Reticulum Stress Driven Immunogenic Cell Death

Abstract: Immunogenic cell death (ICD) is a rare immunostimulatory form of cell death that can improve the clinical outcomes of chemo-immunotherapeutic combination regimens through the establishment of a long-term cancer immunity. None of the clinically used DNA-binding Pt II complexes is considered a Type II ICD inducer. We generated a series of Pt IIcarbene complexes by applying minor structural alterations to the scaffold of a Type II ICD inducer Pt-NHC and compared their efficiency in triggering ICD-related cellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 82 publications
0
4
0
1
Order By: Relevance
“…The comparison between these derivatives showed that the treatment with Pt20 showed the highest levels of the translocation of CRT, the migration of HMGB1, and expression of Hsp90. Interestingly, the activation of ICD‐associated phagocytosis was found to be dependent on the generation of ROS in the ER [26] …”
Section: Pt Complexesmentioning
confidence: 99%
“…The comparison between these derivatives showed that the treatment with Pt20 showed the highest levels of the translocation of CRT, the migration of HMGB1, and expression of Hsp90. Interestingly, the activation of ICD‐associated phagocytosis was found to be dependent on the generation of ROS in the ER [26] …”
Section: Pt Complexesmentioning
confidence: 99%
“…Der Vergleich zwischen diesen Derivaten zeigte, dass die Behandlung mit Pt20 die höchsten Werte für die Translokation von CRT, die Migration von HMGB1 und die Expression von Hsp90 aufwies. Interessanterweise wurde festgestellt, dass die Aktivierung der ICD‐assoziierten Phagozytose von der Erzeugung von ROS im ER abhängt [26] …”
Section: Pt Komplexeunclassified
“…Thus, a combination of PDT and ICD effect has been widely explored for clinical treatment of both superficial tumors and distal tumors [11–16] . Despite the immense achievements, ROS‐triggered immunogenicity is still confronted with some critical challenges, such as the serious O 2 shortage in the hypoxic solid tumors and limited light penetration depth, that enormously diminish the therapeutic outcome [17–24] . In this context, the combination of chemotherapy and ICD effect on the basis of endogenous Type‐I ROS generation would be a more appealing option to improve therapeutic efficacy because it relies lesson O 2 consumption and light irradiation [25–27] .…”
Section: Introductionmentioning
confidence: 99%